A prospective study comparing the efficacy of proximal femoral nail antirotation device with dynamic hip screw fixation in management of unstable pertrochanteric fractures - Thapa, Upendra Jung; Wahegaonkar, Krishna; Ranjeet, Niraj; Sapkota, Krishna; Pratyenta Raj Onta; Thapa, Pabin (Asian Journal of Medical Sciences, 2022)
Background: Pertrochanteric femoral fracture is the most common fractures of the hip especially in the elderly patients with osteoporotic bone, usually due to low-energy trauma like simple falls. Dynamic hip screw (DHS) is still considered the gold standard for treating such factures. Not many studies compare DHS with Proximal Femoral Nail Antirotation (PFNA). We try to compare the efficacy of PFNA with DHS in management of unstable pertrochanteric factors. Aims and Objectives: We aimed to evaluate and compare the clinical and functional outcomes of DHS and PFNA treatment of unstable pertrochanteric femoral fractures in elderly patients. Materials and Methods: This study was a prospective study which included total of 39 patients, 25 patients treated with PFNA and 14 patients with DHS. The study was conducted in Manipal Teaching Hospital from March 1, 2019, to August 1, 2021. All the patients were clinically evaluated and detail history was obtained. After the anesthesia clearance, the patients were operated. Length of skin incision, operating time, intraoperative blood loss, and complications were noted. Postoperatively, the duration of hospital stay, time of partial and full weight-bearing, time for radiological union, and complications were noted. Functional outcome was assessed using Harris hip score at 3 months and 6 months follow-up. Results: The mean age of the patient in this study was 74.68 years for PFNA and 75.57 years for DHS. The average time to complete the surgery was 71 min for PFNA and 92.86 min for DHS. The average blood loss was 162 ml for PFNA and 403 ml for DHS which was found to be statically significant. Partial weight-bearing on axillary crutches was started at the mean time of 3.7 weeks for PFNA and 8.1 weeks for DHS, whereas full weight-bearing was done at the mean of 8.2 weeks for PFNA and 12.1 weeks for DHS. Radiological union was seen at the average of 18.72 weeks for PFNA and 20.14 weeks for DHS which was not statically significant. The mean Harris Hip score at 3 months and 6 months follow-up was 63.84 and 88 for PFNA and 48.50 and 81.43 for DHS, respectively, which showed significantly better result with PFNA. Conclusion: Compared to DHS treatment, PFNA treatment in unstable pertrochanteric femoral fracture is associated with reduced blood loss, shorter operative time, and hospital stay with few intraoperative and post-operative complication. Post-operative rehabilitation with the early mobilization and return to pre-injury status was better with PFNA.